Odpowiedzi

2010-04-08T22:15:49+02:00
A)
4(y-3)-3(x+1) =
4y-12-3x-3 =
4y-3x-15 =
4*2-3*4-15 =
8-12-15 =
-19

b)
3(2b+1)-4(a-2) =
6b+3-4a+8 =
6b-4a+11 =
6*1-4*7+11 =
6-28+11 =
-11

c)
9(x-7y)-(5y-2x)+20y =
9x-63y-5y+2x+20y =
11x-48y =
11*0,5-48*0,3 =
5,5-14,4 =
-8,9

d)
(5x+7y)-8(y+1)+3(x-y) =
5x+7y-8y-8+3x-3y =
8x-4y-8 =
8*½-4*¼-8 =
4-1-8 =
-5
2010-04-08T22:21:20+02:00
Od razu podstawiam i wyliczam
a) 4(2-3)-3(4+1)=-4-15=-19
b)3(2×1+1)-4(7-2)=9-20=-11
c)9(0.5-2.1)-(1.5-1)+6=-14.4-1.5+1+6=-8.9
d)(2.5+1.75)-10+0.75=-5